(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Recently, Electronic Vehicles (EVs) have been attracted substantial responsiveness and so did the advance in battery equipment. Although the battery technology has been significantly advanced, the available batteries do not entirely meet the energy demands of the Electric vehicle power depletion. This latter aspect is very important for urban mobility. Although many EVs are previously available in the market. These topologies of EVs are based on the diverse combination of batteries, fuel cells, super-capacitor, flywheels, and regenerative braking systems, which are used as energy sources and energy storage devices.